Malibu rising [compact disc, unabridged] - Reid, Taylor Jenkins (Random House Audio, 2021)
Four famous siblings throw an epic end-of-summer party that goes dangerously out of control as secrets and loves that shaped this family's generations come to light, changing their lives forever.